A Review of Security Methods in Light Fidelity Technology - Mohammed Majid Msallam; Refik Samet (Proceedings of Engineering and Technology Innovation, 2024)
Light fidelity (Li-Fi) technology is a communication technology using visible light. Li-Fi technology solves the problem of radio frequency bandwidth shortage in wireless fidelity (Wi-Fi) and is more secure considering the wall is impenetrable to the light. However, an exception can be made if a vulnerability emerges when having indoor communication, and the wall leak may induce the hacker to attack the network. Thereby, the encryption data is needed in one or all layers of Li-Fi technology to secure data. This paper presents a review of security threats that need to secure data when using Li-Fi technology to transfer data, and the used methods to secure data in Li-Fi technology are elaborated. A descriptive analysis is also used for related work. As a result, the challenges in Li-Fi technology with encryption used in one of those layers of Li-Fi technology are identified.